2023
DOI: 10.3390/pr11061724
|View full text |Cite
|
Sign up to set email alerts
|

Production of Kojic Acid by Aspergillus niger M4 with Different Concentrations of Yeast Extract as a Nitrogen Source

Abstract: In agro-industrial processes, microorganisms that are not pathogenic and that generate molecules are generally recognized as safe (GRAS). The Aspergillus niger fungus has different industrial applications, being used to produce citric acid and 166 other secondary metabolites. The objective of this research was to optimize a culture medium to induce the production of kojic acid (KA) by the Aspergillus niger M4 strain in a liquid fermentation process. Four fermentative kinetics were developed in flasks, using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…After the fermentation period ended, the biomass was recovered by filtering it through Whatman filter paper (No. 113), washed three times with distilled water, and dried for an entire night at 70 °C to determine its dry mass (DM) [18].…”
Section: Determination Of Dry Weightmentioning
confidence: 99%
“…After the fermentation period ended, the biomass was recovered by filtering it through Whatman filter paper (No. 113), washed three times with distilled water, and dried for an entire night at 70 °C to determine its dry mass (DM) [18].…”
Section: Determination Of Dry Weightmentioning
confidence: 99%
“…For instance, Quiterio-Gutiérrez et al [1] reported the different industrial applications of the non-pathogenic Aspergillus niger fungus. The study dealt with the production of kojic acid by the A. niger M4 strain using different concentrations of yeast extract + Zinc sulfate, which in turn were shown to influence the formation, speed of biomass, synthesis, and yield of Kojic acid.…”
mentioning
confidence: 99%